Analysis of the Application of the Unified Theory of Acceptance and Use of Technology (Utaut) in the Use of Linktree - Istiqomah, Dewi; Hidayatullah, Syarif; Andarwati, Mardiana (PT Inovasi Pratama Internasional, 2024)
Research Aims: Analyze the factors that influence the use of Linktree using UTAUT theory. This research analyzes Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions, Behavioral Intention and Use Behavior in using Linktree by customers. Design/Methodology/Approach: This research examines construction companies that were founded in 2012. Researchers used a sample of 119 customers using Stratified Random Sampling. The analytical method used in this research is UTAUT. Research Findings: Findings show that Performance Expectancy and Effort Expectancy do not have a significant influence on Linktree's Behavioral Intention or Use Behavior. On the other hand, Social Influence and Facilitating Conditions have a significant impact on these two variables. Social Influence influences Behavioral Intention and Use Behavior due to recommendations and social norms received by users. Facilitating Conditions plays an important role in supporting the use of Linktree through the availability of adequate infrastructure and technical support. Apart from that, Behavioral Intention is the most significant factor in determining usage behavior. And the influence of Facilitating Conditions on Behavioral Intention is strengthened when mediated by Use Behavior. Theoretical Contribution/Originality: This research provides a theoretical contribution to the understanding of factors influencing the acceptance and use of new technologies in the context of small and medium-sized companies. Practitioners/Policy Implications: Companies should focus on practical benefits that customers gain, such as easy access to various important links on one page. And considering the significant social influence, marketing strategies must be reinforced with positive testimonials from satisfied customers. Research Limitations/Implications: Companies must focus on the practical benefits of using Linktree, strengthen social influence- based marketing strategies through customer testimonials and recommendations, and ensure conditions that facilitate use remain optimal with adequate infrastructure and technical support.